2015
DOI: 10.1159/000369737
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Lowers Serum Retinol Binding Protein 4 by Suppressing its Expression in Adipose Tissue of Obese Rats

Abstract: Background/Aims: Pioglitazone, a peroxisome proliferator-activated receptor γ activator, is clinically used to treat insulin resistance. However, the underlying mechanism of pioglitazone's action remains unclear. We investigated whether, and how, pioglitazone modulates serum level of retinol binding protein 4 (RBP4), an adipocytokine associated with obesity and insulin resistance. Methods: Insulin sensitivity was determined by oral glucose tolerance test, and RBP4 expression was detected by RT-PCR and Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Intriguingly, our result showed that the RBP4 mRNA expression level in adipose tissue was considerably increased in rats fed HFD. This result is confirmed by the previous study (Zhu et al, 2015). On the other side, the GLUT4 mRNA expression level in adipose tissue was substantially reduced by HFD.…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, our result showed that the RBP4 mRNA expression level in adipose tissue was considerably increased in rats fed HFD. This result is confirmed by the previous study (Zhu et al, 2015). On the other side, the GLUT4 mRNA expression level in adipose tissue was substantially reduced by HFD.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of TZD on the level of retinol in goats in the first experiment is of interest. It has been previously shown that treatment with pioglitazone, a thiazolidinedione molecule, decreased retinol binding protein 4 (RBP) in the serum of rats, as well as decreasing the expression of Rbp4 in 3T3-L1 adipocytes (Zhu et al ., 2015). The reduction of serum retinol by TZD detected in the first experiment can be attributed to the fact that RBP transports retinol in the blood from liver storage to peripheral tissues (Zabetian-Targhi et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, rosiglitazone decreases RBP4 levels in the adipose tissue of Glut4 −/− mice ( 33 ). In addition, pioglitazone significantly decreases levels of RBP4 in an obese rat model, decreases body weight and improves insulin sensitivity ( 94 ). Finally, sitagliptin, a dipeptidyl peptidase-4 inhibitor, decreases RBP4 expression and improves insulin sensitivity in diabetic rats ( 95 ).…”
Section: Clinical Applications Of Rbp4 and Future Perspectivesmentioning
confidence: 99%